Mistranslation and telomere stability - Silva, Filipa Isabel Serra e (2011)
The regulation of a stable proteome is crucial for the cell homeostasis. The translation process from the nucleotide sequence of a gene into the aminoacid sequence of a protein is associated with a basal error of 10-4 which the cell deals with through quality control mechanisms. The misincorporation of aminoacids into de novo synthesized proteins tends to rise when the cell is exposed to stressful conditions. The increase of dysfunctional proteins produced by mistranslation may induce expression of genes related to stress response and genome destabilization. In this work we used yeast as a model to study the impact of high mistranslation rates in telomere stability, since the telomeric and adjacent sub-telomeric regions are key elements on the preservation of genome integrity. Results shown that some types of induced mistranslation may in fact have an impact on telomere length, and also that some proteins’ activity, such as Pnc1 and Sir2, is important regarding telomeric DNA stability. These results shed a new light over the importance of controlling mRNA mistranslation rates in eukaryotic cells.